Efficiency, Productivity and Financial Performance in the Yemen Banking Industry - Abdullah Maram, Mohammed Ali (2010)
Prior to 1990, Yemen was divided into two parts: Yemen Arab Republic and the People's Democratic Republic of Yemen. In May 1990, the two parts were united to form the Republic of Yemen. At the beginning of 1995, the Yemeni government started ambitious plans to reform the fnancial and administrative sectors in all economic institutions, putting in place fnancial and monetary policies which set the bases for the development of Yemeni banking industry. Through the next 19 years, the banking industry in Yemen has undergone a series of changes through fnancial reforms, advancement of communication and information technologies, globalization of fnancial services, and economic development. Through the next 19 years, the banking industry in Yemen has undergone a series of changes through financial reforms, advancement of communication and information technologies, globalization of financial services, and economic development. These changes should have had a considerable efect on eficiency,productivity change, and performance in the banking industry. The motivation of this study is to investigate empirically the impact of these changes on the banking industry. Thus, this study aims to address three main research issues related to the banking industry in Yemen, specifically: 1. Whether reforms of the financial services sector have led to improvement in efciency and productivity gains in Yemen banking industry. 2. Whether banks' eficiency in the banking industry in Yemen is determined by a set of microeconomic variables. 3. Whether the fnancial reforms have influenced the overall operational performance of Yemen banking industry.This study adopts a non-parametric Data E nvelopment Analysis (DE A) and Malmquist Productivity Index (MPI) to measure eficiency and productivity gains of banks in Yemen using financial and other information representing all local banks over a 16 year period from 1992 to 2007. Input and output variables are refined to represent the intermediation role of banks. The estimated eficiency and productivity scores in intermediation models recorded a declining trend in eficiency, and show a negative trend in the first half of the study period from 1992 to 1997. However, in the second half of the study period, the mean eficiency scores of Yemeni banks shows some interesting evidences on the impact of financial and administration reforms in the financial sector. In terms of ownership, the findings show that foreign banks recorded a higher average eficiency than domestic banks and privately-owned banks recorded a relatively higher average eficiency than state-owned banks. The enhanced independence given to boards of management under the globalization process has led not only to improved eficiency in Yemen banking industry, but also to the reduction of the eficiency gap between the state-owned banks and privately-owned banks. In the second part of rst stage in estimating the MPI, the results show that even though banks in Yemen have invested for the advancement in communication and information technologies, no productivity gains have been achieved from improvement of eciency. Nevertheless, the results show that Yemen banks have focused on improving the productivity process. The analysis on determinants of technical eficiency in Yemen banking industry shows that technical eficiency has a positive relationship with variables such as profitability (Return on Assets), capital strength, liquidity, and assets quality. On the other hand, a negative relationship is shown with collateral value. The last investigation used in this study is the application of C AMEL-S model to assess the influence of financial reforms on operational performance pre and post financial reform in Yemen banking industry. The results show that there is a significant improvement in the overall banking performance following the financial reform in Yemen banking industry.